Pemanfaatan Instagram dalam Strategi Komunikasi Pemasaran untuk Promosi UMKM Makanan Mochimoe Bogor Desa Pabuaran Bogor - Pratiwi Sakti, B Retno; Fernanda, Reza; M, Mohammed Achour; Igo, Arif (Jurnal Abdimas Dedikasi Kesatuan, 2026)
ABSTRACT This research is motivated by the significant role of Micro, Small, and Medium Enterprises (MSMEs) as business activities managed by individuals that contribute greatly to job creation and the strengthening of local economies. To support MSME growth, an effective marketing communication strategy is essential to enhance sales performance. One example is Mochi_Moe Bogor, a culinary MSME known for its wide variety of mochi flavors and its contribution to providing employment opportunities for the community in Pabuaran, Bogor Regency. Initially, marketing activities were conducted using conventional methods. However, over time, Mochi_Moe Bogor transitioned to digital marketing through the Instagram platform, utilizing various engaging promotional approaches while still maintaining traditional sales methods. This study refers to the Integrated Marketing Communication (IMC) Theory and the AIDA Model (Attention, Interest, Desire, Action) as theoretical frameworks for analyzing the implementation of marketing communication strategies, including word-of-mouth promotion, digital marketing, and participation in community activities. Based on interviews and observations of the Mochi_Moe Bogor Instagram account, the study concludes that the marketing communication strategies implemented through social media are quite effective. This effectiveness is reflected in the increased attention, interest, and desire of consumers to make purchases, both directly at the store and through online channels. Keywords: Marketing Communication Strategy, Promotion, Integrated Marketing Communication Theory